Pengaruh Green Product, Customer Experience, dan Store Atmosphere terhadap Kepuasan Konsumen Melalui Keputusan Pembelian sebagai Variabel Intervening pada Kopi Janji Jiwa di Jakarta - Astri Putri Maharani; Nova Anggrainie (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The coffee industry in Indonesia is growing rapidly, especially in Jakarta, which is the center of the economy in Indonesia. This tight competition forces Kopi Janji Jiwa to pay more attention to factors that impact consumer satisfaction in order to maintain and increase market share. This study examines the impact of green products, customer experience, and store atmosphere on consumer satisfaction through purchasing decisions at Kopi Janji Jiwa in Jakarta and uses a quantitative method with primary data obtained from 175 respondents who live in Jakarta and have purchased and consumed Kopi Janji Jiwa products. The sampling method was carried out using non-probability sampling and purposive sampling techniques, and using the Hair formula. The research findings show that all independent variables impact consumer satisfaction and all independent variables also influence purchasing decisions. On the other hand, all independent variables influence consumer satisfaction through purchasing decisions as intervening variables at Kopi Janji Jiwa in Jakarta.